Long-term variability and source signature of gases emitted from oil & natural gas and cattle feedlot operations in the Colorado front range. (15th October 2021) - Ortega, I.; Hannigan, J.W.; Buchholz, R.R.; Pfister, G.
Abstract: Multiple tropospheric gases are analyzed in ten years of observations (2010–2019) using a high-resolution ground-based solar absorption Fourier Transform InfraRed (FTIR) instrument in the Colorado Northern Front Range (CNFR). The first year of measurements in 2010 coincides with the start of the remarkable increase of oil and natural (O & NG) extraction in the region. We show seasonal variations and trends of atmospheric gases related to O & NG (C2 H6 ), cattle feedlot activities (NH3 ), urban emissions (CO, C2 H2 ), biomass burning (HCN), and volatile organic compounds related to photochemistry and ozone production (H2 CO, HCOOH). The long-term time series of C2 H6 shows clear episodic peak-enhancements related to local O & NG emissions that contribute to a positive trend of 0.9 ± 0.3 % ⋅yr −1 . NH3 also shows episodic enhancements and has the greatest rate of change for the gases studied here (2.7 ± 0.7 % ⋅yr −1 ). Simulations of all gases are presented using the Community Atmosphere Model with chemistry (CAM-chem) within the Community Earth System Model (CESM) framework. Modeled gases are compared to the observations using different combinations of global emissions in order to determine the best combination for the CNFR. For most gases, using best emissions, the annual rate of change obtained with CAM-chem agrees with the FTIR observations, except for NH3, which is underestimated by a factor of 6. Nevertheless, simulations of NH3 show that the positive trend in NH3 is due to a decrease in its removal via reaction with H2 SO4 from a reduction in coal power plant emissions. The seasonal variations of all gases are generally well represented in the model, although magnitudes are often underestimated. The anthropogenic emissions of CO, C2 H2, and C2 H6 are underestimated by about 20 %, 40 %, and 65 %, respectively, independent of emission inventories. While NH3 summer values are underestimated significantly, other months show low relative mean difference between FTIR observations and CAM-chem simulations. Excellent agreement is found for H2 CO, but for HCOOH a factor of 2–3 is needed in the simulations to match observations, pointing to a significant missing source. HCN, a tracer for biomass burning emissions, is well reproduced by the NCAR Fire Inventory (FINN). Furthermore, we show here a simple approach to identify local enhancements of gases related to nearby O & NG and concentrated animal feeding operations. These enhancements above ambient levels are used to estimate emission ratios (ER) of C2 H6, H2 CO, and HCOOH relative to CO from O & NG air masses. A median ER (and standard deviation) of 0.48 ± 0.41, 0.26 ± 0.15, and 0.13 ± 0.09 [ppb/ppb] are estimated for C2 H6, H2 CO, and HCOOH, respectively and are representative of the ten years of observations. ER can be used to estimate emission factors (EF), although CO emissions from O & NG need to be well-known. To complement the FTIR observations, we show results derived with airborne observations during The Front Range Air Pollution and Photochemical Experiment (FRAPPE) in 2014. Even though FTIR and FRAPPE observations can not be compared easily they both yield similar median ER. Finally, plumes of fires originated in the western United States in August 2015 were identified and EF are estimated. Highlights: NDACC FTIR measurements of 8 tropospheric gases from 2010 to 2021 at Boulder, CO. Trends increasing for C2 H6, NH3, and CH4 and decreasing for CO and C2 H2 . Source emission ratios estimated from enhancements above ambient levels. Excess C2 H6 and NH3 attributed to O&NG and feedlot operations, respectively.